Digital Modernization of Agriculture - Begishev Ildar; Shutova Albina; Vasiliev Yuri; Bersei Diana; Perepadya Olga; Dolgopolov Kirill (BIO Web of Conferences)
The article considers the problems of the need for digitalization of agricultural production, which will increase productivity, competitiveness of agricultural production in Russia and on the global stage. Positive aspects that can be emphasized when using digital technologies are numerous. In general, given their focus on the above-said industry development, we consider it necessary to highlight proposals for further digitalization of the industry, which, as it seems, should lead agriculture to the appropriate transformation as soon as possible.